In Vitro Neuroprotective Effects of a Mixed Extract of Bilberry, Centella asiatica, Hericium erinaceus, and Palmitoylethanolamide - Rebecca Galla; Sara Ferrari; Ivana Miletto; Simone Mulè; Francesca Uberti (Foods)
Oxidative stress, driven by impaired antioxidant defence systems, is a major contributor to cognitive decline and neurodegenerative processes in brain ageing. This study investigates the neuroprotective effects of a natural compound mixture—composed of Hericium erinaceus, Palmitoylethanolamide, Bilberry extract, and Centella asiatica—using a multi-step in vitro strategy. An initial evaluation in a 3D intestinal epithelial model demonstrated that the formulation preserves barrier integrity and may be bioaccessible, as evidenced by transepithelial electrical resistance (TEER) and the expression of tight junctions. Subsequent analysis in an integrated gut–brain axis model under oxidative stress conditions revealed that the formulation significantly reduces inflammatory markers (NF-κB, TNF-α, IL-1β, and IL-6; about 1.5-fold vs. H2O2), reactive oxygen species (about 2-fold vs. H2O2), and nitric oxide levels (about 1.2-fold vs. H2O2). Additionally, it enhances mitochondrial activity while also improving antioxidant responses. In a co-culture of neuronal and astrocytic cells, the combination upregulates neurotrophic factors such as BDNF and NGF (about 2.3-fold and 1.9-fold vs. H2O2). Crucially, the formulation also modulates key biomarkers associated with cognitive decline, reducing APP and phosphorylated tau levels (about 98% and 1.6-fold vs. H2O2) while increasing Sirtuin 1 and Nrf2 expression (about 3.6-fold and 3-fold vs. H2O2). These findings suggest that this nutraceutical combination may support the cellular pathways involved in neuronal resilience and healthy brain ageing, offering potential as a functional food ingredient or dietary supplement.